Porous g‐C3N4 and MXene Dual‐Confined FeOOH Quantum Dots for Superior Energy Storage in an Ionic Liquid. Issue 2 (27th November 2019) - Shi, Minjie; Xiao, Peng; Lang, Junwei; Yan, Chao; Yan, Xingbin
Abstract: Owing to their unique nanosize effect and surface effect, pseudocapacitive quantum dots (QDs) hold considerable potential for high‐efficiency supercapacitors (SCs). However, their pseudocapacitive behavior is exploited in aqueous electrolytes with narrow potential windows, thereby leading to a low energy density of the SCs. Here, a film electrode based on dual‐confined FeOOH QDs (FQDs) with superior pseudocapacitive behavior in a high‐voltage ionic liquid (IL) electrolyte is put forward. In such a film electrode, FQDs are steadily dual‐confined in a 2D heterogeneous nanospace supported by graphite carbon nitride (g‐C3 N4 ) and Ti‐MXene (Ti3 C2 ). Probing of potential‐driven ion accumulation elucidates that strong adsorption occurs between the IL cation and the electrode surface with abundant active sites, providing sufficient redox reaction of FQDs in the film electrode. Furthermore, porous g‐C3 N4 and conductive Ti3 C2 act as ion‐accessible channels and charge‐transfer pathways, respectively, endowing the FQDs‐based film electrode with favorable electrochemical kinetics in the IL electrolyte. A high‐voltage flexible SC (FSC) based on an ionogel electrolyte is fabricated, exhibiting a high energy density (77.12 mWh cm −3 ), a high power density, a remarkable rate capability, and long‐term durability. Such an FSC can also be charged by harvesting sustainable energy and can effectively power various wearable and portable electronics. Abstract : A unique electrode based on dual‐confined FeOOH quantum dots (FQDs) is proposed, in which FQDs are confined in a 2D heterogeneous nanospace supported by g‐C3 N4 and Ti3 C2 . Such an electrode exhibits superior energy‐storage behavior in a high‐voltage ionic liquid electrolyte, introducing a new avenue for breaking the bottleneck of the low energy density of quantum‐dot‐based supercapacitors.